2017
DOI: 10.1016/j.yexcr.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Robo signaling regulates the production of cranial neural crest cells

Abstract: Slit/Robo signaling plays an important role in the guidance of developing neurons in developing embryos. However, it remains obscure whether and how Slit/Robo signaling is involved in the production of cranial neural crest cells. In this study, we examined Robo1 deficient mice to reveal developmental defects of mouse cranial frontal and parietal bones, which are derivatives of cranial neural crest cells. Therefore, we determined the production of HNK1 cranial neural crest cells in early chick embryo developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…3; refs. [43][44][45]. The proteins encoded by these axon guidance and melanogenesis genes demonstrated extensive interactome connectivity (Fig.…”
Section: Functional Pathway Analysismentioning
confidence: 99%
“…3; refs. [43][44][45]. The proteins encoded by these axon guidance and melanogenesis genes demonstrated extensive interactome connectivity (Fig.…”
Section: Functional Pathway Analysismentioning
confidence: 99%
“…In contrast to the skeletal defects in the vertebral column, craniofacial defects of NELL1-deficient mice indicate a deficiency of neural crest cell derivatives (6). Recently, Li et al (26) demonstrated that Robo1 and Robo2 double knockout mouse embryos show the defect of cranial osteogenesis because production of cranial neural crest cells is reduced. The overlapping phenotypes of NELL1-deficient mice and Robo1/2 double knockout mice suggest that they function in a common pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Robo receptors and their Slit ligands form one of the most crucial ligand-receptor pairings among axon guidance molecules. However, Slit/Robo signaling not only functions in axon guidance but also in a variety of developmental events outside the nervous system (26). For example, Slit/Robo signaling is involved in many aspects of heart development, such as cardiac cell migration and alignment (27).…”
Section: Discussionmentioning
confidence: 99%
“…[ 109 ] Slit‐3 axon guidance cues emitting from the skeleton are sensed by nerves through the receptors, Robo1. [ 148–152 ] Ephrin B2, an Eph receptor‐interacting protein which navigates nerve growth, can be identified from osteoclasts and osteoblasts. [ 153 ] Osteoblasts produce Netrin‐1, the receptor of which is well expressed in the nervous system.…”
Section: Possible Signals From Bone To Nerves Within Bonementioning
confidence: 99%